Pressure Distribution in Various Chamber Shapes of an Aerostatic Thrust Bearing Orifice under High Rotational Speeds - Trari, Tayeb; Ghezali, Faiza; Benlefki, Abdelkrim; Yahiaoui , Tayeb (Engineering, Technology & Applied Science Research, 2025)
The purpose of this article is to evaluate the impact of air film thickness and chamber shape on the performance characteristics of an aerostatic thrust bearing operating at ultra-high rotational speeds, including pressure distribution, mass flow rate, load capacity, and stiffness. A three-dimensional Reynolds-averaged Navier-Stokes (RANS) analysis using the SST-kω model is employed to study the effect of supply pressure on various operational and geometric parameters. A comparison between the numerical simulation and experimental data was conducted for chamber shape A to verify the model’s robustness. Both approaches demonstrated good agreement. Pressure distribution and mass flow were examined across different chamber geometries, revealing the presence of inertia effects and gas vortices, which diminish as the air film thickness increases. Further investigation showed that the load capacity of the aerostatic thrust bearing decreases slightly as the rotational speed increases. Additionally, the numerical results indicate significant variations in the performance of the aerostatic thrust bearing depending on the geometry of the orifice chamber.